Genetic and non-genetic factors affecting disposal up to first calving in Karan Swiss cattle - SINGH, M K; GURNANI, M (The Indian Journal of Animal Sciences, 2014)
A study was conducted on the factors and mode of culling and mortality up to first calving in 1992 Karan Swiss females born during 1982 to 1992 at National Dairy Research Institute, Karnal. The culling and mortlity rates accounted for 13.4 and 26.1% of herd strength. Inbreeding, age group and year of birth have significantly affected the disposal rate. Maximum mortality (70% of total loss) was observed up to the age of 3 months. The respiratory and digestive disorders were the primary causes. The extreme climatic conditions resulted in higher incidences of mortality. Significantly adverse effect of inbreeding above 6% coefiicient was observed on survivability at early ages. The mortality up to first calving varied from 7.8 to 28.0% and the culling rates over the years ranged from 17.2 to 35.0%. Poor growth, late maturity, reproductive disorders. foot problems and diseases were important causes of culling and accounted for 8.5, 3.73.2,2.9 and 2.8% of herd strength, respectively. Culling at early ages was mainly due to poor growth and health disorders and at later ages was mainly due to late maturity and infertility problems. The present study suggested the improvement in nutritional status, effective prevention and medication measures and keeping inbreeding under safer limit.